2017
DOI: 10.1111/jop.12582
|View full text |Cite
|
Sign up to set email alerts
|

Oral submucous fibrosis: An update on pathophysiology of malignant transformation

Abstract: Oral submucous fibrosis (OSMF) is a potentially malignant condition associated with areca nut chewing. Formerly confined to the Indian subcontinent, it is now often seen in Asian populations of the United Kingdom, USA and other developed countries, and is therefore a serious problem for global health. What makes it more sinister is the malignant transformation rate, which has been reported to be around 7.6% over a 17-year period. In this concise article, we review the current trends in the pathophysiology of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…() on human fibroblasts treated with arecoline support the point that accelerated fibroblast proliferation and up‐regulated collagen formation occur in OSF tissues. Meanwhile differential alterations of cell cycle‐related proteins which can be crucial in the various stages of arecoline‐mediated carcinogenesis, reported by a review on pathophysiology of malignant transformation about OSF (Arakeri et al., ). Another study revealed that the hydrolysis of arecoline into arecaidine promoted collagen synthesis in OSF FBs.…”
Section: Discussionmentioning
confidence: 99%
“…() on human fibroblasts treated with arecoline support the point that accelerated fibroblast proliferation and up‐regulated collagen formation occur in OSF tissues. Meanwhile differential alterations of cell cycle‐related proteins which can be crucial in the various stages of arecoline‐mediated carcinogenesis, reported by a review on pathophysiology of malignant transformation about OSF (Arakeri et al., ). Another study revealed that the hydrolysis of arecoline into arecaidine promoted collagen synthesis in OSF FBs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with OSMF have been reported with higher risk of developing oral squamous cell carcinoma (OSCC), compared to other OPMD's [71,72]. Although 7.6% of OSMF cases transformed to oral squamous cell carcinoma (OSCC) in a 17-year follow up study reported in 1970 [73], other studies with smaller follow up periods report malignant transformation rates ranging from 1.9-9%, [74][75][76] depending on diagnostic criteria and duration of follow up [77]. Studies suggest that malignant transformation in patients with OSMF differs from those without OSMF.…”
Section: Malignant Transformation Of Osmfmentioning
confidence: 99%
“…OSF has been frequently reported in South Asia and parts of East Africa (Tilakaratne et al, 2006). About 7%-13% of them eventually transformed into oral squamous cell carcinoma (OSCC) (Chaturvedi et al, 2013;Arakeri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%